FBXL14 abolishes breast cancer progression by targeting CDCP1 for proteasomal degradation. Issue 43 (25th October 2018) - Cui, Yan-Hong; Kim, Hyeonmi; Lee, Minyoung; Yi, Joo; Kim, Rae-Kwon; Uddin, Nizam; Yoo, Ki-Chun; Kang, Jae; Choi, Mi-Young; Cha, Hyuk-Jin; Kwon, Ok-Seon; Bae, In-Hwa; et al.
Abstract Understanding the molecular mechanisms that underlie the aggressive behavior and relapse of breast cancer may help in the development of novel therapeutic interventions. CUB-domain-containing protein 1 (CDCP1), a transmembrane adaptor protein, is highly maintained and required in the context of cellular metastatic potential in triple-negative breast cancer (TNBC). For this reason, gene expression levels ofCDCP1 have been considered as a prognostic marker in TNBC. However, not rarely, transcript levels of genes do not reflect always the levels of proteins, due to the post-transcriptional regulation. Here we show that miR-17/20a control the FBXL14 E3 ligase, establishing FBXL14 as an upstream regulator of the CDCP1 pathway. FBXL14 acts as an novel interaction partner of CDCP1, and facilitates its ubiquitination and proteasomal degradation with an enhanced capacity to suppress CDCP1 protein stability that eventually prevents CDCP1 target genes involved in breast cancer metastasis. Our findings first time uncovers the regulatory mechanism of CDCP-1 protein stabilization, more predictable criteria than gene expression levels for prognosis of breast cancer patients.